2023
DOI: 10.1021/acsanm.2c05136
|View full text |Cite
|
Sign up to set email alerts
|

CoSe2 Nanoparticles with Multienzymic Activities for Antibacterial Applications

Abstract: Increasing bacterial resistance has led to the aggravation of diseases caused by microbial infections, posing a significant threat to human health. The multicascade approach is more efficient than a single treatment for resistant bacteria. Here, we describe the simple method of fabricating CoSe 2 nanoparticles, which operate as a single-component, multienzyme-mimicking nanoplatform for multiple ROS production. The nanoplatform simultaneously exhibits multienzymatic activities that mimic intrinsic catalase, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Bacterial infection has become one of the most serious threats to human health in the world, which induces a huge medical and financial burden to our society. Antibiotics are considered a good choice to combat bacterial infection. Undoubtedly, the application of antibiotics has reduced morbidity and mortality significantly. However, in the past few decades, the overuse and abuse of antibiotics has led to the constant emergence of drug-resistant bacterial strains, and antibiotics have become less effective .…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infection has become one of the most serious threats to human health in the world, which induces a huge medical and financial burden to our society. Antibiotics are considered a good choice to combat bacterial infection. Undoubtedly, the application of antibiotics has reduced morbidity and mortality significantly. However, in the past few decades, the overuse and abuse of antibiotics has led to the constant emergence of drug-resistant bacterial strains, and antibiotics have become less effective .…”
Section: Introductionmentioning
confidence: 99%
“…The catalase activity of MoO 3−x /Cu was assessed by the change in fluorescence intensity of EuTc-HP at 620 nm produced by the combination of H 2 O 2 and europium tetracycline (EuTc). 47 In addition, oxygen produced by CAT-like activity in the presence of nanoenzymes was further assayed using a dissolved oxygen instrument. 48 Supporting Information provides detailed information.…”
Section: Characterization Of Pod Oxd and Cat Activitiesmentioning
confidence: 99%
“…48 EuTc-based fluorometric assay was used to study the catalase-like activity of the samples. 47 EuTc and H 2 O 2 can generate a europium tetracycline-hydrogen peroxide complex (EuTc-HP) with enhanced fluorescence intensity at 620 nm. Nanoenzymes with CAT-like activity can decompose H 2 O 2 , and the synthesis of EuTc-HP decreases, which leads to a weakening of the fluorescence intensity.…”
mentioning
confidence: 99%
“…However, recent studies have revealed that Co‐based nanozymes can possess photothermal properties that respond to NIR (808 nm), which have already been shown to be effective in more efficient antibacterial applications. [ 99 ] Nonetheless, the photothermal conversion performance of these nanozymes is currently insufficient to realize photothermal therapy (PTT) of tumors. Consequently, exploring the mechanisms and enhancing the photothermal properties of these nanozymes can pave the way for expanding their applications.…”
Section: Unique Properties Of Co‐based Nanozymesmentioning
confidence: 99%
“…In this context, CoSe 2 nanoparticles synthesized by Xu and colleagues exhibited simultaneous CAT‐like, POD‐like, and OXD‐like activities. [ 99 ] Furthermore, the photodynamic multienzyme cascade and ROS generated by these nanoparticles significantly inhibit drug‐resistant, broad‐spectrum β ‐lactamase‐producing Escherichia coli under the synergistic influence of 808 nm near‐infrared radiation.…”
Section: Biomedical Therapymentioning
confidence: 99%